Pulmonary toxicity following total body irradiation for acute lymphoblastic leukaemia: The Ottawa Hospital Cancer Centre (TOHCC) experience. Issue 1 (2nd November 2015) - Ujaimi, R. K.; Isfahanian, N.; Russa, D. J. La; Samant, R.; Bredeson, C.; Genest, P.
Abstract: Purpose: To review the incidence of clinically significant pulmonary toxicity following total body irradiation (TBI) as a part of the conditioning regimen for acute lymphoblastic leukaemia (ALL) patients undergoing bone marrow transplantation (BMT) at The Ottawa Hospital Cancer Centre. Methods: This is a retrospective review of ALL patients who received TBI in The Ottawa Hospital Bone Marrow Transplant Program (TOH-BMT) as part of their conditioning regimen from 1991 to 2011 inclusive. The patients were treated using a locally developed translating-couch irradiation technique. We have analysed all available data for the first 100 days following TBI to determine the incidence of radiation-induced pulmonary toxicities. Results: Of the total 622 patients undergoing TBI during the specified period, 88 had ALL. Median age at BMT was 30 years and the conditioning regimens varied. A total of 74 (84%) patients received 12 Gy/6 F/BID of TBI. A total of 55 (63%) patients have died, 32 (36%) within the 1st year after BMT. In the 1st year, pulmonary events were reported for 24 (27%) patients, and the follow-up notes were unavailable for seven (8%). Pulmonary toxicities were reported as the cause of death for six patients, five (6%) within the 1st year. It is estimated that the total number of deaths in the 1st year possibly attributed to radiation-induced lung injury was four (4·5%). Eight (9%) patients had symptoms suggestive of non-lethal grade 2–3 radiation-induced pneumonitis. Conclusions: TBI continues to be an important component of the conditioning regimen for ALL patients undergoing BMT, and the incidence of radiation-induced pulmonary injury, using our technique and lung dose, is comparable to the published literature.